MEASUREMENT OF DIELECTRIC LOSS OF ICE Ih AT MICROWAVE FREQUENCIES WITH CAVITY RESONATOR - マツオカ, タケシ; フジタ, シュウジ; モリシマ, シゲノリ; マエ, シンジ; MATSUOKA, Takeshi; FUJITA, Shuji; MORISHIMA, Shigenori; MAE, Shinji (National Institute of Polar Research, 1995)
P(論文) The relative complex dielectric permittivity (ε^*=ε′-iε″) of ice Ih was measured at 5GHz and 10GHz by the cavity resonator method in the temperature range -60℃ to -3℃. The purpose of this study was to clarify the temperature dependence and frequency dependence of dielectric loss (tanδ=ε″/ε′) of ice at microwave frequencies. Because the values of dielectric loss of ice strongly contribute to the penetration depth of microwaves in ice, investigation of the dielectric loss of ice is important for analysis of microwave remote sensing data of the cryosphere. The cavity resonator method is suitable for low loss materials such as ice. Ice samples were polycrystalline and made from distilled and deionized water. The experimental results were as follows : The values of dielectric loss increased as the temperature increased. The values were 1.0∿2.2×(10)^<-4> at 10GHz and 0.6∿1.4×(10)^<-4> at 5GHz in the temperature range -60℃ to -3℃. The gradients of dielectric loss versus temperature (dtanδ/dT) also increased as the temperature increased. The values of penetration depth in ice at 5GHz and 10GHz were about 80m and 14m at -60℃, 35m and 10m at -3℃, respectively. departmental bulletin paper